Políticas educacionais da diversidade : narrativas de experiências dos docentes-ativistas por uma pedagogia do multiculturalismo - Caetano, Carlos Alberto (2020)
This thesis is part of the research line School Organization, Training and Pedagogical Practices of the Graduate Program in Education at the Federal University of Mato Grosso which has as its central question: How do the activists-teachers perceive their experiences in view of the constitution of political guidelines diversity and how do they present themselves in the context of the struggle for social justice? This thesis is characterized, methodologically, by a qualitative approach, with a focus on narrative research based on Clandinin and Connelly (2015), who defend narrative research as a method and phenomenon, based on Dewey (1979) based on the concept of experiences on education. The research involved nine activist teachers. For the composition of field texts that were used: autobiographical writing, photographs, official narratives, conversations and in- depth narrative interviews. The general objective is: To understand the experiences of the activist-teachers in the constitution of educational policies of diversities in the education systems of Mato Grosso. The composition of the senses took place through the intertwining of three great narratives: the First Narrative, called the Autobiographical Narrative, the Second Narrative constituted by the official narratives and the Third Narrative by the reports of the teacher-activists, organized in three axes of analysis: Personal experiences and professionals with diversity; Learning and meanings for performance, Training in and for diversity. The reflections were based on, Bauman (1997), Fanon (1975), Gadamer (1998), Hall (2015), Day (2001), Garcia (1999), Moore (2007), Nascimento (1996; 1999; 2007; 2010), Zeichner (2010); Santos (2003; 2006; 2013; 2018), Nogueira (2007), Castles and Miller (2004), Calloni (2002), Maar (1994), Canen; Oliveira (2002), Craveiros; Medeiros (2013), Munanga (1995), among others. The results of the analyzes show that the teaching-activists have been supporting practical fields of epistemo-political action, which constitute their own curricular and didactic- pedagogical procedures, with their identity praxis, matured, experienced and experienced in the daily life of quilombola education. This epistemo-policy, of the teachers-activist in the context of diversities, builds a praxis-educator a critical pedagogy, which in addition to teaching-learning, is anchored in principles aimed at the pursuit of social justice, based on a political-educational practice resignified by multicultural heritage, for the uniqueness and affirmation of identity. Finally, they show us that there is an educational praxis constituted amid the conflicting contextuality of educational policies of diversity that can be characterized by a pedagogy of multuculturalism.